2014
DOI: 10.1177/0957650913517677
|View full text |Cite
|
Sign up to set email alerts
|

Selection and thermodynamic analysis of a turbocharger for a producer gas-fuelled multi-cylinder engine

Abstract: The current work addresses the use of producer gas, a bio-derived gaseous alternative fuel, in engines designed for natural gas, derived from diesel engine frames. Impact of the use of producer gas on the general engine performance with specific focus on turbo-charging is addressed. The operation of a particular engine frame with diesel, natural gas and producer gas indicates that the peak load achieved is highest with diesel fuel (in compression ignition mode) followed by natural gas and producer gas (both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This assessment is based on previous experience with PG fueled operation wherein it has been observed that under naturally aspirated and stoichiometric operation, the peak load delivered by the engine is limited to about 4.65 kWe per litre of swept volume. The factors contributing to power derating and the corresponding recovery options have been discussed by Dasappa [43] and the authors [27] elsewhere.…”
Section: Engine and Instrumentation Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment is based on previous experience with PG fueled operation wherein it has been observed that under naturally aspirated and stoichiometric operation, the peak load delivered by the engine is limited to about 4.65 kWe per litre of swept volume. The factors contributing to power derating and the corresponding recovery options have been discussed by Dasappa [43] and the authors [27] elsewhere.…”
Section: Engine and Instrumentation Specificationmentioning
confidence: 99%
“…The highest calorific value at 2.41 MJ/kg is however lower than NG calorific value of 2.5 MJ/kg (conservative estimate based on 45 MJ/kg fuel calorific value and 17:1 air to fuel ratio). The reduced mixture energy density coupled with lower CR results in engine power de-rating [27,43]. Hydrogen with high thermal conductivity/diffusivity adds significantly to the mixture conductivity/diffusivity, potentially enhancing the convective heat losses from the engine.…”
Section: Evaluation Of Calorific Value Specific Heat Thermal Conducmentioning
confidence: 99%
“…Producer gas (PG) is one such renewable fuel [2] which can meet this twin requirement of being renewable and carbon neutral via biomass gasification technology [3]. According to literature, a typical biomass based power generation would reduce approximately 30 % CO 2 emissions annually as compared to coal fired thermal power plant [4]. Literature reveals that in Europe about one million engines were powered via gasifiers during World War-II and the technology soon disappeared due to easy availability of baseline (fossil) liquid fuels [5].…”
Section: Introductionmentioning
confidence: 99%
“…This has led the automotive manufacturer to introduce downsizing concepts that optimize a suitable compression ratio necessary for turbocharging. Recent developments have been made in NA engines for which design parameters at higher compression ratio are brought equivalent to a lower compression engine by means downsizing technique which usually accommodates a turbocharger, this offers enhanced charge cooling, knock free operation, and effective scavenging of the residual gases to improve the low-end torque (Shivapuji and Dasappa 2014), (Padmavathi R, Nandhakumar K 2010). The mass and energy transfer becomes essential parameters that determine a turbocharger's performance, which is necessary for matching.…”
mentioning
confidence: 99%